THE INFLUENCE OF THE RENAISSANCE’S ART OF MEMORY ON DESCARTES’ PHILOSOPHY - Gintautas Mažeikis (Problemos, 1998)
The Renaissance’s sources of Descartes’ method are discussed in this article. Main attention is paid to the cabbalistic principles of Ramon Lull’s "Short Art" and Brunian and Ramist art of memory. Descartes knew Lull’s art to which he reffered to in very derogatory terms. The same logical, Pythagorean, and cabbalistic principles of Lullism, however, became the basis for the art of memory of the Renaissance and for the natural magic of the Renaissance, which Descartes knew. The occult art of memory of the Renaissance is also considered. J. Bruno was a great follower of occult art of memory and of the system of Lullism. The art of Peter Ramus arises to counterpose the official Catholic system of memory and the occult art of memory in the Protestant countries. The chief aim of the Ramist movement for the reform and simplification of education was to provide a new and better way of memorizing the subject. This was to be done using a new method, whereby every subject was to be arranged in a "dialectical order." Descartes exercised his great mind on the art of memory and how it might be reformed. The mnemonic author who gave rise to his reflections was Lambert Schenkel. Descartes interpreted the traditional sacral Medieval art of memory and Renaissance occult art of memory as "corporeal memory" and "outside of us" as compared with "intellectual memory", which is within us and incapable of increase or decrease. There is a hypothesis that the art of memory, radical doubt, and some ideas of the Protestant movement were the sources of Descartes’ scientific method.